Interactive fuzzy satisfying‐based HVDC/AC transmission expansion planning considering investment cost and network loss. (18th April 2016) - Doagou‐Mojarrad, Hasan; Rastegar, Hasan; Gharehpetian, Gevork B.
Summary: In this paper, a novel Multi‐objective Modified Binary Particle Swarm Optimization (MBPSO) algorithm is used to solve the transmission expansion planning (TEP) problem. Minimization of total investment cost and power loss are the objective functions of this problem, which are modeled by fuzzy sets. The problem is transformed into a mini‐max case with an improved human–machine interface. According to the technical merits of HVDC system, HVDC links is introduced as a candidate solution for TEP problem. Finally, the proposed algorithm is tested on two test systems, and the HVDC links effects on TEP problem are investigated. The simulation results demonstrate that these lines play an important role in the reduction of network loss and subsequent investment costs. Copyright © 2016 John Wiley & Sons, Ltd.